Profitabilitas dan Pengungkapan Corporate Social Responsibility pada Nilai Perusahaan BUMN - Aula Nurul Ma’rifah; Andri Andri; Dewi Tradena (Jurnal Ekonomi & Bisnis, 2023)
Competition in the business world is increasingly complex so that companies are required to be able to maintain their survival because company value is an indicator of business development showing the condition of the company on public trust in company performance as well as a description of future prospects. However, some BUMNs are experiencing problems so that it is feared that it will affect the company's future value. In this situation, the company needs to maintain and increase its company value by knowing what factors can underlie this situation so that it can minimize conditions that are not good for the company. This study aims to determine the effect of profitability and corporate social responsibility disclosure on firm value in Indonesia Stock Exchange. This research method is quantitative research with secondary data and a research sample of 14 companies. Data analysis in this study used multiple linear regression. The results showed that the profitability variable was able to affect firm value while CSR (Corporate Social Responsibility) disclosure had no effect on firm value.